Sweeping up the heart - Henkes, Kevin (Greenwillow Books, 2019)
Seventh-grader Amelia Albright goes on an adventure with a new friend, Casey, who claims to have seen the spirit of Amelia's deceased mother. Instead of going on a spring break trip to Florida, Amelia is forced to stay home, but that week spent with her first male friend is both thrilling and daunting.